analisis analisis kemampuan pemahaman konsep matematika pada soal cerita materi pengukuran peserta didik kelas III SD Negeri 2 Kepatihan: analisis kemampuan pemahaman konsep matematika pada soal cerita materi pengukuran peserta didik kelas III SD Negeri 2 Kepatihan - Diyah Nur Cahyaningtyas; Alik Mustafidal Laili (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research stems from several challenges observed among lower-grade primary school students, including: limited understanding of basic mathematical concepts; difficulty translating word problems into mathematical expressions; inability to complete mathematical sentences; lack of care in calculations; and errors in writing mathematical symbols. The aim of this research is to describe students’ conceptual understanding in solving word problems on measurement, based on Bloom’s (1956) indicators: translation, interpretation, and extrapolation. This study uses a qualitative phenomenology method with eight word problems as research instruments. The subjects of this study were 17 students from SD Negeri 2 Kepatihan. Data collection was conducted through tests, interviews, and documentation. The results show that 9 out of 17 students scored between 39–51, with an overall average score of only 59.7. This indicates that students’ conceptual understanding of mathematics is still low. The findings suggest the need for efforts to improve students’ conceptual understanding and for teachers to innovate in their teaching strategies.